2022
DOI: 10.1002/ajh.26569
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin light chain amyloidosis: 2022 update on diagnosis, prognosis, and treatment

Abstract: Disease overview Immunoglobulin light chain amyloidosis is a clonal, nonproliferative plasma cell disorder in which fragments of immunoglobulin light or heavy chain are deposited in tissues. Clinical features depend on organs involved but can include heart failure with preserved ejection fraction, nephrotic syndrome, hepatic dysfunction, peripheral/autonomic neuropathy, and “atypical smoldering multiple myeloma or monoclonal gammopathy of undetermined significance (MGUS).” Diagnosis Tissue biopsy stained with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 120 publications
(197 reference statements)
0
41
0
1
Order By: Relevance
“…However, a phase III, randomized, open-label, multicenter study showed no benefit from the addition of doxycycline in patients with cardiac involvement ( 25 ). It is well established that the extent of heart involvement in patients with amyloidosis is the major determinant of survival ( 26 ). In our analysis, the median OS from diagnosis to last follow-up or death was 14 months (range, 0.5-120 months).…”
Section: Discussionmentioning
confidence: 99%
“…However, a phase III, randomized, open-label, multicenter study showed no benefit from the addition of doxycycline in patients with cardiac involvement ( 25 ). It is well established that the extent of heart involvement in patients with amyloidosis is the major determinant of survival ( 26 ). In our analysis, the median OS from diagnosis to last follow-up or death was 14 months (range, 0.5-120 months).…”
Section: Discussionmentioning
confidence: 99%
“…Patients with systemic AL amyloidosis who were newly diagnosed by renal biopsy in Xijing Hospital (Xi’an, China) from December 2015 to March 2021 were included in our study. The diagnosis of systemic AL amyloidosis was confirmed by the presence of apple-green birefringence under polarized light after Congo red staining and the identification of fibrils with a diameter of 8–12 nm by electron microscopy ( 22 ). Patients who suffered from diabetes, membranous nephropathy, IgA nephropathy, or other confounding diseases based on relevant clinical and pathological information were excluded.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the diagnostic workup generally involves amyloid typing and ruling out a systemic B-cell lymphoproliferative disorder (most commonly systemic AL amyloidosis, multiple myeloma, and B-cell lymphoma). Therefore, testing should be performed to a) confirm immunoglobulin-derived amyloid fibrils with typing, ideally via liquid chromatography-tandem mass spectrometry (LC-MS/MS) ( 31 ), b) evaluate for evidence of a clonal plasma cell or B-cell population, c) rule out systemic organ involvement with AL amyloidosis, and d) characterize potential manifestations of localized organ involvement ( 32 34 ).…”
Section: Diagnosismentioning
confidence: 99%